Pelaksanaan Tanggung Jawab Sosial Di Perusahaan Swasta Nasional Dan Badan Usaha Milik Negara - Saputra, Argadwi; Agustina Gultom, Indriati; Irsandi, Irsandi (Jurnal Syntax Fusion, 2023)
This research aims to analyze and know the implementation and sanction of Corporate Social Responsibility at National Private Company and State Owned Company. This research was conducted at PT Keong Nusantara Abadi Lampung and PT PLN (Persero) Lampung Distribution, and Lampung CSR Forum. The research method used is the normative and empirical juridical approach, which is done by examining the library materials consisting of secondary data and primary data, then data analysis is done by qualitative juridical analysis. Implementation of CSR in National Private Companies and State-Owned Enterprises have differentiation and similarity this is due to the different implementation of the legal basis, but in principle the implementation of CSR aims to improve the economy and prosper the community, in addition sanctions for companies that do not implement Corporate Social Responsibility is not clearly regulated in law in Indonesia, but if CSR is not implemented then the company will get moral sanction from society, which resulted in decreasing public trust.Implementation